2023
DOI: 10.3390/vaccines11030516
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Vaccine Attitudes Influenced by the COVID-19 Pandemic

Abstract: The development of vaccines has significantly contributed to the success of disease prevention. However, there has been a sharp decline in immunization rates since COVID-19 spread globally. Seemingly overnight, the world shut down and most non-essential medical procedures were postponed. Since the COVID-19 vaccine became available, and the world started going back to normal these vaccine rates have not recovered. In this paper, we review the published literature to explore how convenience factors, perceived ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 77 publications
1
22
1
Order By: Relevance
“…By contrast, the current study found that adolescents’ unwillingness to be vaccinated influenced vaccination decisions even if parents were willing, but this was only in a minority of cases. The COVID-19 pandemic has influenced vaccine attitudes [ 24 ], which may explain some differences in our findings compared with findings from earlier studies.…”
Section: Discussioncontrasting
confidence: 71%
“…By contrast, the current study found that adolescents’ unwillingness to be vaccinated influenced vaccination decisions even if parents were willing, but this was only in a minority of cases. The COVID-19 pandemic has influenced vaccine attitudes [ 24 ], which may explain some differences in our findings compared with findings from earlier studies.…”
Section: Discussioncontrasting
confidence: 71%
“…Wales public data reported 2022–23 1 st dose in 1 st year uptake of 12.3% in Wales (all genders) increasing to 69.1% in year 2 of school (72.8% in girls and 65.6% in boys) [ 18 ]. This pattern aligns to the sharp declines observed in immunisation rates globally since the COVID-19 pandemic [ 19 ].…”
Section: Introductionsupporting
confidence: 75%
“…This decline in HPV vaccination uptake may be due to multiple complex factors [ 20 ]. At the beginning of the pandemic, the World Health Organisation (WHO) advised postponement of immunisation programmes to enable IMNs to focus on administration of COVID-19 vaccines [ 19 ]. This has created a backlog of immunisations placing additional workload pressures on IMN teams [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few very recent works talk about the impact of the COVID-19 pandemic on the traditional non-COVID vaccines, such as MMR, IPV, etc. However they only comprise of anectodal evidence (Altman et al 2023;Knijff et al 2023) and rudimentary surveybased analyses (Rivera-Rivera et al 2023). Our study is the first to analyse the impact of COVID-19 on opinions towards the non-COVID vaccines on a large scale over social media.…”
Section: Related Workmentioning
confidence: 99%